Study regarding the prediction of medal winning in Olympic Games judo competitions - Lascau, F. D.; Rosu, D. (Journal of Physical Education and Sport, 2013)
Problem Statement: The Olympic Games are the lead competition for any sport, and the ultimate goal of any sportsman, national federation or coach is to obtain the Olympic medal. The analysis of the ways to attain this goal fully justifies the efforts of sports specialists around the world. This research analyzes the official interim rankings determined during the Olympic cycle and the extent to which they matched the final rankings at the London Olympic Games 2012. Approach: The 56 Olympic medals awarded in 2012 were retrospectively analyzed in conjunction with the World Ranking List on which the qualifying for the Olympic Games (top 4 and top 8) was based, with the results of the latest World Championships (top 4 and top 2011, Paris) as well as with results in previous Olympic Games (top 4 and top 8 2008, Beijing). Purpose: Analyze the interim rankings during an Olympic cycle in judo in order to reveal the most predictable of them with a view to obtaining medals in the Olympic Games. Results: The results of 6 rankings were presented with statistical data support in form of frequencies and percentages, including calculations of the arithmetic means of percentages, of standard deviations and of variability coefficient. The study of distributions revealed abnormal distribution in the 2nd weight category for both men and women, which is something that requires a special scientific approach. Conclusions: World Ranking List-Top 8 predicted best, on average, the Olympic results to an extent of 81%, and the World Championships Top 8 - 2011 to an extent of 70% without including the women`s 52 kg and men`s 66 kg categories, statements made with moderate reliability. The other analyzed rankings revealed a low prediction rate and too wide dispersion to be worth considering. The renewal rate of the elite echelon (new medal winners) from one Olympics to the next stands at around 80%.